2002
DOI: 10.1007/bf02701696
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing gas evolution on graphite and oxygen-evolving anodes

Abstract: Recent progress in material science might soon allow the replacement of the consumable carbon anode by an inert material. This is likely to induce changes in the overall process, and particularly in the gas evolution. Video recordings of oxygen-evolving anodes (SnO 2 , Cu, Cu-Ni) and carbon anodes were performed in laboratory electrolysis cells, using direct observation from above, a see-through cell, and radiography techniques. The gas behavior was very different between the two kinds of anodes, and probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 2 publications
1
59
0
1
Order By: Relevance
“…Therefore, it may be more likely that variation in wetting is due to variation in isotropy or possibly impurity concentrations, as also suggested by Qiu et al [47]. The wetting angle of graphite with cryolite electrolyte in this study (~100°) was slightly lower than that recorded in other studies (120-130° [16]), possibly due to material or electrolyte composition differences.…”
Section: Characterisation Of Anode Surface and Interfacial Propertiessupporting
confidence: 46%
See 1 more Smart Citation
“…Therefore, it may be more likely that variation in wetting is due to variation in isotropy or possibly impurity concentrations, as also suggested by Qiu et al [47]. The wetting angle of graphite with cryolite electrolyte in this study (~100°) was slightly lower than that recorded in other studies (120-130° [16]), possibly due to material or electrolyte composition differences.…”
Section: Characterisation Of Anode Surface and Interfacial Propertiessupporting
confidence: 46%
“…Results in this study were similar to that found by Xue and Øye [12] -their 10 mm diameter graphite anode evolved one main bubble, leaving the anode surface completely free of bubbles afterwards. However, larger anodes are thought to sustain several bubbles simultaneously [16]. The magnitude of voltage variation of graphite recorded in other studies at 1 A cm -2 has been lower; for example 0.1 V [22] or 0.3 V [21], but in both cases discrepancies are most likely related to the geometry of the anode.…”
Section: Electrochemical Measurements Of Bubble Evolutionmentioning
confidence: 86%
“…In pottery and tile manufacture, SnO 2 has been used as opacifier in glazes [14] and as raw material for the chrome-tin pink and some other pigments [15]. Along the last decades, it has been increasingly used in components requiring high chemical corrosion resistance in chemical industry applications [16,17]. In the last field, an important application is obtaining electrodes for electric glass melting furnaces [18,19] and the processing of aluminium by electrolysis [17,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Along the last decades, it has been increasingly used in components requiring high chemical corrosion resistance in chemical industry applications [16,17]. In the last field, an important application is obtaining electrodes for electric glass melting furnaces [18,19] and the processing of aluminium by electrolysis [17,20,21]. Stoichiometric tin oxide is a good insulator at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of simulating electrolytically formed bubbles in molten salts was solved by the authors of [6][7][8][9][10][11][12][13]. The investigation of the fluid dynamics phenomena occurring during the electrolysis was required using the low-temperature model.…”
Section: Physical Simulationmentioning
confidence: 99%